Chlamydia trachomatis in Iceland: Prevalence, Clinico-epidemiological Features and Comparison of Cobas 480 CT/NG and Aptima Combo 2 (CT/NG) for Diagnosis - Ingibjorg Hilmarsdóttir; Eva Mjöll Arnardóttir; Elísabet Reykdal Jóhannesdóttir; Daniel Golparian; Magnus Unemo (Medical Journals Sweden, 2021)
The aims of this study were to assess the prevalence of, and risk factors for, Chlamydia trachomatis in attendees recruited prospectively from October 2018 to January 2019 at the only sexually transmitted infections clinic in Iceland (in Reykjavík), and to evaluate the cobas 4800 CT/NG Test and Aptima Combo 2 Assay for C. trachomatis detection in male urine and female vaginal swabs. Prevalence of C. trachomatis was 15.8% among 487 women and 13.6% among 491 men (no Neisseria gonorrhoeae positive patients were found). C. trachomatis detection was independently and positively associated with being tested for contact tracing, 18-24 years of age, and reporting ≥ 6 sexual partners within 12 months. Reporting sex with non-residents of Iceland was associated with a lower risk of C. trachomatis infection. Both assays had a high sensitivity in detection of C. trachomatis (Aptima Combo 2: 100%; cobas 4800 CT/NG: 95.1%) and high specificity (100% and 99.6%, respectively). The high local prevalence of C. trachomatis and increased acquisition risk following sex with residents are of public health concern.